Literasi Edukasi Mengenai Bahaya Cyberbullying Terhadap Konsep Diri Siswa di SMA Al-Ma’aruf Cibubur - Murtanti Putri, Dianingtyas; Risma Dedees, Adek (LPkM Universitas Bakrie, 2024)
Current technological advancements have facilitated various aspects of life for those who utilize them. However, the use of technology, particularly in communication and various other sectors, often lacks corresponding responsibility for its impacts. One significant negative impact is the rise in cyberbullying cases, which not only causes distress but also affects the process of an individual's self-concept formation. In fact, victims of cyberbullying require considerable time to recover from its psychological effects. Considering this phenomenon, our Community Service Program (PkM) will focus on providing explanations about media literacy, specifically the dangers of cyberbullying and its effect on individual self-concept formation. The goal of this initiative is to offer guidance and education on responsible social media usage to 11th and 12th-grade students at Al’Ma’ruf High School in Cibubur, East Jakarta. Responsibility here means that every user should be aware that messages conveyed, both verbally and non-verbally, carry meanings and impacts. These messages can influence the cognitive, affective, and conative aspects of the individuals receiving them. Furthermore, to ensure the effectiveness of this activity, psychological support and effective coping strategies are essential. This support is necessary to help mitigate negative impacts and foster the recovery of a positive self-concept by implementing the Do's and Don’ts provided by facilitators, who can also serve as agents of change among their peers.